The Influence of Financial Rewards, Work Environment, and Personality Type on Accounting Students' Interest in Pursuing a Career as a Public Accountant (Study on Accounting Students of Majalengka University) - Pamuji, Rita Silvia; Saparinda, Raden Wulan; Rusdiana, , Alan; Rofi’i, Agus (Junal Ilmu Manajemen, 2025)
This study aims to analyze the impact of Financial Rewards, Work Environment, and Personality Types on Accounting Students' Interest in becoming public accountants. The research employs Structural Equation Modeling-Partial Least Squares (SEM-PLS) methodology. Data analysis was conducted using SmartPLS software, involving two main stages: estimating the structural model through the PLS Algorithm and testing significance using Bootstrapping. The results from the PLS Algorithm indicate that both Financial Rewards and Work Environment hurt Accounting Students' Interest, while Personality Types show a positive effect. However, the significance test results from Bootstrapping reveal that only Personality Types have a significant impact, with a t-value of 2.338 (>1.96), whereas the effects of Financial Rewards and Work Environment are not significant. Additionally, an R-square value of 0.215 indicates that 21.5% of the variability in students' interest can be explained by this model. Based on these findings, it can be concluded that Personality Types are the most influential factor affecting Accounting Students' interest in pursuing a career as a public accountant.